Spinning dreams - Leong, Bei Yi (Nanyang Technological University, 2021)
“Spinning Dreams” is a 2D animated short film created by Li Xuan Wei, Loh Kee and Leong Bei Yi. It aims to touch the hearts of people who have experienced a similar journey. Another purpose is to learn new software to create 2D animation such as Toon Boom Harmony. Before creating "Spinning Dreams" the group did a brief historical research on ancient Chinese culture. The storyboard, animatic, and rough animation then followed. Final clean-ups and colouring were done in Toon Boom Harmony. Through the research, the group noted the difference between Chinese animation in Western Companies and Chinese Companies. "Spinning Dreams" animation is mixture of Chinese and Western style that give it uniqueness. Overall, "Spinning Dreams" uses different approaches to create a visual animation and appeals audiences who relates to the story.